(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2012)
There are two basic categories oftechnologies that convert sunlight into useful forms of energy, aside frombiomass-based systems that do this in a broader sense by using photosynthesisfrom plants as an intermediate step. First, solar photovoltaic (PV) modulesconvert sunlight directly into electricity. Second, solar thermal power systemsuse focused solar radiation to produce steam, which is then used to turn aturbine producing electricity. The following provides a brief overview of thesetechnologies, along with their current commercial status.